2014
DOI: 10.1155/2014/594287
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta (TGF-β) Signaling in Paravertebral Muscles in Juvenile and Adolescent Idiopathic Scoliosis

Abstract: Most researchers agree that idiopathic scoliosis (IS) is a multifactorial disease influenced by complex genetic and environmental factors. The onset of the spinal deformity that determines the natural course of the disease, usually occurs in the juvenile or adolescent period. Transforming growth factors β (TGF-βs) and their receptors, TGFBRs, may be considered as candidate genes related to IS susceptibility and natural history. This study explores the transcriptional profile of TGF-βs, TGFBRs, and TGF-β respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 81 publications
1
14
0
1
Order By: Relevance
“…Runx2 is a key transcription factor regulating osteogenesis in response to canonical Wnt44 and transforming growth factor-beta (TGF-β)45, thus representing an early bone formation marker. The observed Runx2 down-regulated expression in AIS suggests impaired osteogenic differentiation ability, which was in line with previous etiopathogenetic studies4647. Osteoblasts regulate osteoclasts activities through the release of receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG).…”
Section: Discussionsupporting
confidence: 89%
“…Runx2 is a key transcription factor regulating osteogenesis in response to canonical Wnt44 and transforming growth factor-beta (TGF-β)45, thus representing an early bone formation marker. The observed Runx2 down-regulated expression in AIS suggests impaired osteogenic differentiation ability, which was in line with previous etiopathogenetic studies4647. Osteoblasts regulate osteoclasts activities through the release of receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG).…”
Section: Discussionsupporting
confidence: 89%
“…Abnormalities in TGF-β signalling are associated with several musculoskeletal disorders, including Duchenne muscular dystrophy [51], and it is a known inducer of muscle atrophy through induction in expression of muscle-specific ligase Atrogin-1 [19]. It is notable, therefore, that a recent study reported differential expression of TGF-β and TGF-β receptors with upregulation of TGF-β-responsive genes in paravertebral muscles from the concave side of the curve apex compared with the convex side [44]. This data is indicative of abnormal TGF-β signalling in the paravertebral muscles of patients with AIS and could therefore be a contributory factor to the abnormal paraspinal muscle pathology observed in AIS patients.…”
Section: Paraspinal Musclesmentioning
confidence: 99%
“…Analysis of the TGF-beta responsive genes differentiating both sides of the paravertebral muscle transcriptomes of AIS patients highlighted the upregulation of genes localized in the extracellular region of the curve concavity (latent TGF-beta binding proteins: LTBP3, LTBP4 and integrins: ITGB4, ITGB5). This could suggest extracellular matrix of paravertebral muscles as an interesting target for future molecular research [2]. At present treatment of IS is symptomatic and involves bracing and severe surgery.…”
Section: Short Communicationmentioning
confidence: 99%